(3GdehGLgI GdLfGFjI dLQGFe GdEQgGH aj GdJTQjY GdGeGQGJj (B:s (3OQGSI ebGQfI (B/ s - (3UbQ Sja Hf CMeO GdfbHjs; (3TQja SjO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JfGhdJ aj gPg GdOQGSI GdehGLgI GdLfGFjI dLQGFe GdEQgGH aj GdJTQjY GdGeGQGJj, hgOaJ Edi HjGf GdCMcGe GdehVhYjI hGdELQGFjI dLQjeI GdEQgGH, hGSJNOeJ GdefgL GdhUaj GdJMdjdj hGdefgL GdebGQf, hbSeJ GdOQGSI Edi HGHjf NUUJ GdChd deGgjI GdEQgGH hUhQg aj GdJTQjY GdEeGQGJj, ceG beJ HJejjRg YeG jTJHg Hg, hNUUJ GdHGH GdKGfj ddCMcGe GdELQGFjI dLQjeI GdEQgGHjI, aj eQMdI LeY GdGSJOdGdGJ, heQMdI GdJMbjb GdGHJOGFj, Ke eQMdI GdeMGceI(B. (3hJhUdJ dYOO ef GdJhUjGJ ef CgegG(B: (3Ydi GdeTQY GdGJMGOj JhSjY fWGb GdELQGAGJ GdGSJKfGFjI GdebQQI aj bGfhf ecGaMI GdEQgGH GdGJMGOj Qbe (B7 (3dSfI (B2014 (3Edi GdLQGFe GdeGSI HCef GdOhdI GdOGNdj(B. (3ceG Ydi GdeTQY GdGJMGOj EYGOI GdfXQ aj UjGZI GdeGOJjf (B29 (3h (B30 (3ef GdbGfhf Qbe (B7 (3dSfI (B2014 (3aj TCf ecGaMI GdLQGFe GdEQgGHjI dJLfH GdCdaGX GdecQQI hHPdc Jchf CcKQ hVhMkG(B. (3ceG jLH Cf JMGW eQMdJj GdHMK hGdJaJjT hGdJMbjb HVeGfGJ bVGFjI, jQGYj ajgG Mbhb GdEfSGf, dCf GdeJge HQF MJi JKHJ EOGfJg HeMGceI bVGFjI YGOdI(B.s
In this study, I dealt with the criminal confrontation of terrorism crimes in the UAE legislation, and aimed to clarify the objective and procedural provisions for the crime of terrorism, and I used the analytical descriptive approach and the comparative approach. The second is for the procedural provisions of the terrorist crime, in the evidence-gathering stage, the preliminary investigation stage, and then the trial stage. It reached a number of recommendations, the most important of which are: The federal legislator should expand the scope of the exceptional measures established in the Federal Anti-Terrorism Law No. 7 of 2014 to crimes affecting the internal security of the state. The federal legislator should also reconsider the wording of Articles 29 and 30 of Law No. 7 of 2014 regarding combating terrorist crimes in order to avoid repetitive terms and thus be more clear. The research, inspection and investigation phases must also be surrounded by judicial guarantees, in which human rights are taken into account, because the accused is innocent until proven guilty in a fair judicial trial.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2023 s
(3HHdjhLQGajG(B: (3UaMGJ (B399-434.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdGQgGH ai GdbGfhf GdGeGQGJis; (3GdJMbjb GdGHJOGFj dLQGFe GdGQgGHs; (3eQGbI GdeMGOKGJs; (3GdefY ef GdSaQs; (3Zdb GdGeGcfs; (3YOe GdJbGOe dLQjeI GdGQgGHs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs